Assessing and Unlocking the Value of Emerging Markets Sustainability Indices - Lubin, David; Esty, Dan; Lauterbach, Sandra; Miller, Deborah; Raza, Yamama; Masland, John (International Finance Corporation, Washington, DC, 2017)
This report explores the rapid expansion of sustainability indices in emerging markets and the potential of these indices to support broader sustainability efforts. It looks at 17 emerging market sustainability indices, comparing and contrasting business models, sustainability objectives, and construction methodologies, and identifying obstacles in establishing a viable business model. Specifically, this report examines three related questions: 1) why are emerging markets sustainability indices being launched? 2) What role can these indices play in adding value for investors and other stakeholders? 3) How can index providers and other market players enhance the potential for emerging markets sustainability indices to add value to investors and other stakeholders? With this report, IFC wants to initiate a dialogue on a stronger and more durable business model for emerging markets sustainability indices. The study was commissioned by IFC in partnership with the Swedish International Development Cooperation Agency in addition to Ireland, Italy, Luxembourg, the Netherlands and Norway; and was conducted by Esty Environmental Partners.